Optical Coherence Tomography in Stargardt’s Dystrophy - Samsel, Agnieszka; Dróbecka-Brydak, Ewa; Brydak-Godowska, Joanna; Ciszewska, Joanna; Kęcik, Dariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Stargardt's disease is one of the central retinal dystrophies with its onset in first two decades of life presenting gradual decrease in visual acuity and typical features in fluorescein angiography. The aim of the study was to evaluate the macular area in patients with diagnosed Stargardt's disease with the use of optical coherence tomography. 11patients (22 eyes) were enrolled to the study. OCT examination revealed characteristic similar features of macular images in all patients. They included decreased thickness of the retina, most prominent in foveola, and changes in external retinal layers: lack of photoreceptors and nuclear external layer and changes in retinal pigment epithelium. Because of typical features in macular appearance, optical coherence tomography may become a useful tool for confirming diagnosis of Stargardt's disease.